1992
DOI: 10.1111/j.1365-2648.1992.tb01968.x
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction of nursing staff working in hospitals

Abstract: Job satisfaction remains an important consideration for both employer and employee and, despite numerous investigations, many questions about it remain unanswered. Many research methodologies have been used with varying degrees of success. However, the trend is now away from simple correlational studies towards modelling techniques. Data from 221 female nurses working full-time in hospitals were collected using questionnaires delivered with monthly salary cheques. The model presented had many statistically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
3
21

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 15 publications
1
67
3
21
Order By: Relevance
“…Sixty eight (35.4%) of respondents had believe that staff turnover can cause decrease in productivity whereas 46(24%) had believed that staff turnover can cause decreased spread of organizational knowledge. In line with this research, several studies have shown the relationship between nurses' working conditions, such as high workload, and job dissatisfaction [11]. Job dissatisfaction of nurses can lead to low morale, absenteeism, turnover, and poor job performance, and potentially threaten patient care quality and organizational effectiveness [12].…”
Section: Discussionmentioning
confidence: 88%
“…Sixty eight (35.4%) of respondents had believe that staff turnover can cause decrease in productivity whereas 46(24%) had believed that staff turnover can cause decreased spread of organizational knowledge. In line with this research, several studies have shown the relationship between nurses' working conditions, such as high workload, and job dissatisfaction [11]. Job dissatisfaction of nurses can lead to low morale, absenteeism, turnover, and poor job performance, and potentially threaten patient care quality and organizational effectiveness [12].…”
Section: Discussionmentioning
confidence: 88%
“…For instance, Fung-kam (1998) found that the three factors that have the most influence on job satisfaction were autonomy, professional status, and pay. Many studies do not find pay to be associated with overall job satisfaction among RNs (Butler and Parsons, 1989;Cavanagh, 1992;Reineck and Furino, 2005). On the contrary, Williams (1990) and Best and Thurston (2006) found pay satisfaction and autonomy the most important components of overall job satisfaction in a sample of Canadian nurses.…”
Section: Pay Satisfaction Job Satisfaction and Turnover Intentmentioning
confidence: 99%
“…A insatisfação expressa quanto à avaliação pode estar ligada à manutenção de um processo (avaliação) cujos resultados não têm expressão ao nível da progressão na carreira. Os mesmos resultados foram obtidos por outro investigador que no seu modelo teórico estabelece precisamente a relação entre educação, oportunidade, integração e justiça e a insatisfação no trabalho (17) .…”
Section: Métodosunclassified